Epidemiological Profile and Outcome of Pregnancy Associated Acute Kidney Injury (TAJ: Journal of Teachers Association, 2023)
Background: In developing countries, pregnancy-associated acute kidney injury (PAAKI) is a significant cause of maternal and neonatal mortality and morbidity. A systematic evaluation is essential to understand its frequency and severity in our setting.  Objectives: Primary aim of our study was to evaluate the epidemiological profile and outcome of patients with pregnancy-associated acute kidney injury.  Patients and Methods: The study was conducted in the Department of Nephrology, Rajshahi medical college hospital, from January 2019 to March 2020. A total of 83 patients with pregnancy-associated acute kidney injury were evaluated. Patients who had a history of chronic kidney disease or were diagnosed as a case of chronic kidney disease were excluded from the study.Result: The mean age±SD was 25.39±5.90 years. The majority were